231k views
5 votes
Which equation is y = 9x2 + 9x – 1 rewritten in vertex form?

2 Answers

3 votes

Answer:

The vertex form of a parabolic function has the general formula:

f(x) = a(x-h)^2 + k where (h,k) represent the vertex of the parabola.

Therefore, to write the given equation in vertex form, we will need to transform it to the above formula as follows:

y = 9x^2 + 9x - 1

y = 9(x^2 + x) - 1

y = 9(x^2 + x + 1/4 - 1/4)-1

y = 9((x+1/2)^2 - 1/4)-1

y = 9(x + 1/2)^2 - 9/4 - 1

y = 9(x + 1/2)^2 - 13/4 ..............> The equation in vertex form

Explanation:

Hope this helps!!! Have a great day!!! : )

User Jprim
by
6.3k points
2 votes

Answer:


y = 9(x +(1)/(2)) ^ 2 -(13)/(4)

Explanation:

An equation in the vertex form is written as


y = a (x-h) + k

Where the point (h, k) is the vertex of the equation.

For an equation in the form
ax ^ 2 + bx + c the x coordinate of the vertex is defined as


x = -(b)/(2a)

In this case we have the equation
y = 9x^2 + 9x - 1.

Where


a = 9\\\\b = 9\\\\c = -1

Then the x coordinate of the vertex is:


x = -(9)/(2(9))\\\\x = -(9)/(18)\\\\x = -(1)/(2)

The y coordinate of the vertex is replacing the value of
x = -(1)/(2) in the function


y = 9 (-0.5) ^ 2 + 9 (-0.5) -1\\\\y = -(13)/(4)

Then the vertex is:


(-(1)/(2), -(13)/(4))

Therefore The encuacion excrita in the form of vertice is:


y = a(x +(1)/(2)) ^ 2 -(13)/(4)

To find the coefficient a we substitute a point that belongs to the function
y = 9x^2 + 9x - 1

The point (0, -1) belongs to the function. Thus.


-1 = a(0 + (1)/(2)) ^ 2 -(13)/(4)


-1 = a((1)/(4)) -(13)/(4)\\\\a = (-1 +(13)/(4))/((1)/(4))\\\\a = 9

Then the written function in the form of vertice is


y = 9(x +(1)/(2)) ^ 2 -(13)/(4)

User Raman
by
5.7k points